Robot-assisted minimally invasive thoraco-laparoscopic esophagectomy versus minimally invasive esophagectomy for resectable esophageal adenocarcinoma, a randomized controlled trial (ROBOT-2 trial) - Tagkalos, E.; van der Sluis, P. C.; Berlth, F.; Poplawski, A.; Hadzijusufovic, E.; Lang, H.; van Berge Henegouwen, M. I.; Gisbertz, S. S.; Müller-Stich, B. P.; Ruurda, J. P.; Schiesser, M.; Schneider, P. M.; et al. (BMC cancer, 2021)
Background For patients with esophageal adenocarcinoma or cancer of the gastroesophageal junction, radical esophagectomy with 2-field lymphadenectomy is the cornerstone of the multimodality treatment with curative intent. Both conventional minimally invasive esophagectomy (MIE) and robot assisted minimally invasive esophagectomy (RAMIE) were shown to be superior compared to open transthoracic esophagectomy considering postoperative complications. However, no randomized comparison exists between MIE and RAMIE in the Western World for patients with esophageal adenocarcinoma. Methods This is an investigator-initiated and investigator-driven multicenter randomized controlled parallel-group superiority trial. All adult patients (age ≥ 18 and ≤ 90 years) with histologically proven, surgically resectable (cT1-4a, N0–3, M0) esophageal adenocarcinoma of the intrathoracic esophagus or adenocarcinoma of the gastroesophageal junction and with European Clinical Oncology Group performance status 0, 1 or 2 will be assessed for eligibility and included after obtaining informed consent. Patients ( n = 218) with resectable esophageal adenocarcinoma of the intrathoracic esophagus or adenocarcinoma of the gastroesophageal junction are randomized to either RAMIE ( n = 109) or MIE ( n = 109). The primary outcome of this study is the total number of resected abdominal and mediastinal lymph nodes specified per lymph node station. Conclusion This is the first randomized controlled trial designed to compare RAMIE to MIE as surgical treatment for resectable esophageal adenocarcinoma or adenocarcinoma of the gastroesophageal junction in the Western World. The hypothesis of the proposed study is that RAMIE will result in a higher abdominal and mediastinal lymph node yield specified per station compared to conventional MIE. Short-term results and the primary endpoint (total number of resected abdominal and mediastinal lymph nodes per lymph node station) will be analyzed and published after discharge of the last randomized patient within this trial. Trial registration ClinicalTrials.gov Identifier: NCT04306458 . Registered 13th March 2020, https://clinicaltrials.gov/ct2/show/NCT04306458; Date of first enrolment 18.01.2021; Target sample size 218; Recruitment status: Recruiting; Protocol version 2; Issue date 10.03.2020; Rev. 02.02.2021; Authors ET, PCvdS, PPG.